1987
DOI: 10.1104/pp.84.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of Ribosome Binding to Thylakoid Membranes

Abstract: Previous work indicated more polysomes bound to pea (Pisum sativum cv Progress No. 9) thylakoids in light than in the dark, in vivo (LE Fish, AT Jagendorf 1982 Plant Physiol 69: 814-825). With isolated intact chloroplasts incubated in darkness, addition of MgATP had no effect but 24 to 74% more RNA was thylakoid-bound at pH 8.3 than at pH 7. Thus, the major effect of light on ribosome-binding in vivo may be due to higher stroma pH. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Assessment of the effects of antibiotics on protein synthesis in chloroplasts provides important information regarding the basic features of the chloroplast translation system, which also remains to be fully characterized. Certain antibiotics have previously been shown to inhibit chloroplast translation in organello, and perturb development in vivo (Conte et al 2009;Harris et al 1994;Day and Goldschmidt-Clermont 2011;Eichacker et al 1990;Ellis 1969Ellis , 1971Hurewitz and Jagendorf 1987;Kim et al 1994). In order to collect comparative information, such as dose-dependency, among antibiotics that affect chloroplast protein synthesis, we examined the direct effects of antibiotics on translation activity in our chloroplast extract.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of the effects of antibiotics on protein synthesis in chloroplasts provides important information regarding the basic features of the chloroplast translation system, which also remains to be fully characterized. Certain antibiotics have previously been shown to inhibit chloroplast translation in organello, and perturb development in vivo (Conte et al 2009;Harris et al 1994;Day and Goldschmidt-Clermont 2011;Eichacker et al 1990;Ellis 1969Ellis , 1971Hurewitz and Jagendorf 1987;Kim et al 1994). In order to collect comparative information, such as dose-dependency, among antibiotics that affect chloroplast protein synthesis, we examined the direct effects of antibiotics on translation activity in our chloroplast extract.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies in Chlamydomonas and pea concluded that chloroplast translation always initiates in the stroma and that some ribosomes subsequently become coupled to the thylakoid membrane via the nascent peptide (32,33). Later reports identified several chloroplast mRNAs that are translated in association with the thylakoid membrane, but the results were sometimes conflicting (22,34,35).…”
Section: Discussionmentioning
confidence: 98%
“…Given the altered pigmentation of prpl28‐1 mutant seeds, it can be speculated that the formation of the photosynthetic machinery, which is associated with the greening process, is disturbed. For instance, a specific role of PRPL28 in the translation process on the surface of thylakoid membranes might be hypothesised (Minami and Watanabe, 1984; Hurewitz and Jagendorf, 1987; Zhang et al. , 1999).…”
Section: Discussionmentioning
confidence: 99%